2016
DOI: 10.4314/jab.v100i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and agronomic characterization of 56 ginger landraces in Burkina Faso

Abstract: Objective: This study aims to characterize and assess the variability within the ginger accessions growing in Burkina Faso for morphometric and agronomic traits in order to identify appropriate strategies for the future breeding program. Methodology and Results: The experiment was conducted with 56 accessions in Randomized Complete Block Design with four replications. Moderate diversity was observed for morphometric and agronomic characters. The linear Pearson's correlations between rhizome yield and rhizome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
1
1
0
1
Order By: Relevance
“…The correlation result in this study showed that rhizome yield would improve with an increase in pseudo-stem diameter, plant height, leaf width, and the number of leaves plant −1 . This result aligned with earlier studies (Lincy et al, 2008;Nandkangre et al, 2016) that reported a significant positive correlation of rhizome yield with pseudo-stem diameter, plant height, leaf length and width, number of leaves plant −1 and number of tillers plant −1 . Tall plants with broad leaves tend to have better photosynthetic capacity than plants with narrow leaves (Wang et al, 2019).…”
Section: Crop Sciencesupporting
confidence: 92%
See 1 more Smart Citation
“…The correlation result in this study showed that rhizome yield would improve with an increase in pseudo-stem diameter, plant height, leaf width, and the number of leaves plant −1 . This result aligned with earlier studies (Lincy et al, 2008;Nandkangre et al, 2016) that reported a significant positive correlation of rhizome yield with pseudo-stem diameter, plant height, leaf length and width, number of leaves plant −1 and number of tillers plant −1 . Tall plants with broad leaves tend to have better photosynthetic capacity than plants with narrow leaves (Wang et al, 2019).…”
Section: Crop Sciencesupporting
confidence: 92%
“…The dendrogram grouped the ginger genotypes based on their high-and low-performing attributes compared with the population mean. Variation in rhizome yield and biochemical composition of ginger germplasm has been linked to their genetic differences (Chukwudi et al, 2020;Eleazu et al, 2012;Kizhakkayil & Sasikumar, 2012;Nandkangre et al, 2016;Pattnaik et al, 2016;Sendanayake et al, 2017). Pattnaik et al (2016) showed genetic variability in 20 elite ginger genotypes in India using cluster analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Originaire d'Asie du sud-est (Preeti et al, 2008), le gingembre est cultivé essentiellement pour ses rhizomes. C'est l'une des plus importantes épices au monde de par son importance économique et ses nombreuses vertus médicinales (Nandkangre, 2015). Les nombreuses vertus médicinales (amélioration de la qualité du sperme, protection de l'Acide Désoxyribonucléique, anticoagulant, anti-hypercholestérolémie, antihyperglycémiant, antispasmodique, antimicrobien, etc.)…”
Section: Introductionunclassified